Study of mango biomass (Mangifera indica L) as a cationic biosorbent - Ashraf, M.A.; Maah, M.J.; Yusoff, I. (CTR Environment & Energy Research & Studies, 2010)
Unfertilizable fruiting buds of mango plant Mangifera Indica L, an agrowaste, is used as a biomass in this study. The efficacy of the biosorbent was tested for the removal of lead, copper, zinc and nickel metal ions using batch experiments in single and binary metal solution under controlled experimental conditions. It is found that metal sorption increases when the equilibrium metal concentration rises. At highest experimental solution concentration used ( 150 mg/L), the removal of metal ions were 82.76 % for lead, 76.60 % for copper, 63.35 % for zinc and 59.35 % for nickel while at lowest experimental solution concentration (25 mg/L), the removal of metal ions were 92.00% for lead, 86.84 % for copper, 83.96 % for zinc and 82.29 % for nickel. Biosorption equilibrium isotherms were plotted for metal uptake capacity (q) against residual metal concentrations (C(f)) in solution. The q versus C f sorption isotherm relationship was mathematically expressed by Langmuir and Freundlich models. The values of separation factor were between zero and one indicating favourable sorption for four tested metals on the biosorbent. The surface coverage values were approaching unity with increasing solution concentration indicating effectiveness of biosorbent under investigation. The non-living biomass of Mangifera indica L present comparable biosorption capacity for lead, copper, zinc and nickel metal ions with other types of biosorbent materials found in literature and is effective to remove metal ions from single metal solutions as well as in the presence of other co-ions with the main metal of solution.